Effects of home delivery on colostrum avoidance practices in North Wollo zone, an urban setting, Ethiopia: a cross sectional study - Nigus Bililign Yimer; Misgan Legesse Liben (BMC, 2018)
Abstract Background Colostrum is the first liquid that is produced in the first few days after delivery. It is the perfect first food for newborns which is considered as an infant's first immunization. Despite of this fact colostrum is discarded as unclean and bad for the infant's health. This study aimed to investigate the prevalence and the factors associated with colostrum avoidance in Woldia, Kobo and Lalibela town administrations of North Wollo zone. Methods A quantitative community based cross sectional study was employed in March 2015 on 810 mothers of children aged less than 24 months. Descriptive statistics, binary and multivariable logistic regression analysis were employed to identify the factors associated with colostrum avoidance. Variables with a p-value < 0.05 in the multivariable model were identified as predictors of colostrum avoidance practices. Results Colostrum was discarded by 12.0% (95%CI: 10.0-14.0%) of mothers of children aged less than 24 months. In multivariable logistic regression analysis late initiation of breastfeeding [AOR (95% CI) =2.03 (1.18, 3.49)], prelacteal feeding [AOR (95% CI) =3.38 (1.83, 6.24)], mothers not living with their husband [AOR (95% CI) = 2.24 (1.22, 4.12)] and delivering the index child at home [AOR (95% CI) =2.92 (1.521, 5.59)] were independent positive predictors of colostrum avoidance practices. Conclusion The foundation of any nutrition package for the prevention of childhood malnutrition is the promotion of an optimal breastfeeding practices, including colostrum feeding, in the community. Therefore, promoting institutional delivery, early initiation of breastfeeding and creating awareness on the dangers of prelacteal feeding and the advantages of colostrum feeding are recommended interventions to reduce colostrum avoidance practices in the study area.